Influence of air flow interruption on the total nonelastic resistance of respiration - T. N. Bodrova (Бюллетень сибирской медицины)
The total nonelastic work of respiration (TNWR) was studied in 18 healthy people and 11 patients with the chronic obstructive pulmonary disease with the aid of simultaneous recording of transpulmonary pressure and volume. It was found that under the conditions of identical pulmonary minute volume at air flow interruption by valve, TNWR becomes larger compared to that at quiet deep breathing. The additional resistance was called acophased and was considered as a manifestation of independent mechanical pulmonary activity.